Le golfe du Lion Un observatoire de l'environnement en Méditerranée - Monaco , André; Ludwig , Wolfgang; Provansal , Mireille; Picon , Bernard (éditions Quae, 2009)
The ORME programme (Observatoire régional méditerranéen de l'environnement) is a CNRS multidisciplinary research structure that studies the environment as a scientific object and centres its work on the Gulf of Lion, a land-sea system seen as a key zone in the Mediterranean.This takes stock of the multidisciplinary knowledge acquired of the system. It provides an overview of its vulnerability in the face of climate and manmade change. It demonstrates the necessity of integrated management of the "water" resource, in consultation with all the stakeholders involved, taking account of the interactions between man and nature.